Turbulence of the Modern World through the Prism of the Coronavirus Pandemic - K. S. Gadzhiev (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
The article analyzes some, in the opinion of the author, key factors that determine the nature and consequences of the coronavirus pandemic, which has a more or less significant effect on the turbulent state of the modern world, giving it special specificity, additional significance and irreversible character. Having analyzed a number of pandemic assessments and ideas popular in the scientific literature for the state and prospects of the modern world, it is concluded that with all the possible reservations in this matter, the coronavirus pandemic can be considered as one of the most important factors enhancing the significance of those tectonic shifts in the basic infrastructures of the modern world, which serve as the basis for a change in the liberal/ unipolar world order by a new type of world system. It is shown that the pandemic exposed those pain points that, by definition, are characteristic of transition periods or the so-called axial times. It is accompanied by an exacerbation of contradictions and conflicts between nations, hostility and demonization of the enemy and, accordingly, various forms of racism, xenophobia. Having critically analyzed the ideas about the revival of the positive role of the national state, the supposed end of globalization, the “post-coronavirus world”, the so-called “new normality”, etc., their author’s interpretation is given. Of course, a significant place is given to a comparative analysis of the issues concerning the forms and ways of solving the problems caused by the coronavirus pandemic by different countries.